1999
DOI: 10.1159/000030405
|View full text |Cite
|
Sign up to set email alerts
|

Results and 10-Year Follow-Up in Patients with Squamous Cell Carcinoma of the Penis

Abstract: Penile malignancies are infrequent but represent a diagnostic and therapeutic challenge as patients tend to disregard early asymptomatic lesions of the disease. Due to the lack of studies involving large patient numbers, the therapeutic concepts for different stages of the disease could not be defined by prospective studies. Long-term results are rare. We present the therapeutic concepts and the 10-year results of our experience with 42 cases of penile carcinoma treated at our institution between 1973 and 1986… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Inguinal lymphadenectomy, in addition to being potentially curative, also provides the pathologic lymph node status, the most important prognostic information in penile squamous cell carcinoma (14). The criteria for selection of patients for ilioinguinal lymphadenectomy remain controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inguinal lymphadenectomy, in addition to being potentially curative, also provides the pathologic lymph node status, the most important prognostic information in penile squamous cell carcinoma (14). The criteria for selection of patients for ilioinguinal lymphadenectomy remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been successful (8,14,21,(23)(24). Lopes found that superficially invasive (1 to 5 mM) grade 1 or 2 tumors infrequently rarely metastasized (1 of 24) while deeply invasive ( more than 5 mM) and Grade 3 tumors usually metastasized (43 of 52) (24).…”
Section: Discussionmentioning
confidence: 99%
“…The exceptional occurrence of squa- Emasculation is selectively performed in patients with large tumours infiltrating surrounding structures (T4). After radical surgery, the local recurrence rate ranges from 0 to 14% of cases, with mean values up to 4-5% (table 1) [7][8][9][10][11][12][13][14][15]. Considering the classical criteria of oncological radicality, the issue about the compromise of the penile anatomic and functional integrity inevitably arises, causing a high rate of sexual, psychological and social repercussions.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph nodes, however, frequently undergo reactive enlargement in primary penile cancer [1,21]. This may explain the relatively high rate of false-positive lymph node findings [7,22]. The advantage of crosssectional imaging, particularly CT and MRI, over physical examination is that the former can help to detect deep lymph nodes and masses in the pelvis and retroperitoneum [6].…”
Section: Cross-sectional Imagingmentioning
confidence: 99%